Research on FBG pressure sensor of flat diaphragm structure - Yanling Xiong; Jing He; Wenlong Yang; Linwen Sheng; Wei Gao; Yang Chen (2012 International Conference on Measurement, Information and Control, 2012)
In this paper, a FBG pressure sensor encapsulated by flat diaphragm structure is designed based on the strain characteristic of optical fiber Bragg grating (FBG) and seepage sensing principle. The structure and parameters of sensor are simulated and optimized using ANSYS finite element analysis software based on the mechanics model of flat diaphragm. The metalized FBG is processed into FBG pressure sensor, and the experimental system of flat diaphragm FBG pressure sensor is established. The theoretical and experimental results show that the pressure sensitivity coefficient of flat diaphragm FBG pressure sensor, whose measuring range is 0.5MPa, is 2.3×10 -3 (MPa) -1 , and the linearity is 0.9720. The linearity of flat diaphragm structure is poor within 9KPa, which indicate that the flat diaphragm structure encapsulation is more suitable for the sensors in large measuring range.